Produksi Bioplastik Poli (3-Hidroksibutirat) (P(3HB)) Secara Proses Fermentasi Menggunakan Bakteri Bacillus brevis FAAC-20801 Dari Minyak Kelapa Sawit Sebagai Sumber Karbon - Krisyanella Krisyanella; Mimi Susanti; Akmal Djamaan (STIFARM Padang, 2010)
The production of bioplastic P(3HB) with fermentation process by Bacillus brevis FAAC-20801 from palm oil as carbon has been carried out. The fermentation process was conducted throug at pH 7, 37oC and agitation rate of 200 rpm for 60 hours. The characterization of the bioplastic production was based on cell growth, P(3HB) content and P(3HB) percentage. Results showed that the optimum time was 48 hours, with fermentation biomassa 277 mg, P(3HB) content of 7.2 mg/ 20 mg biomassa (36 % b/b). Fermentation process in bioreactor produced P(3HB) higher than in rotary shaker incubator.